PERAN METODE UMMI DALAM MENGEMBANGKAN KETERAMPILAN MEMBACA DAN MENGHAFAL ALQUR’AN SISWA SEKOLAH DASAR ISLAM ATHIRAH BUKIT BARUGA MAKASSAR - Saidah, Saidah (Inspiratif Pendidikan, 2016)
This thesis discusses the role of Ummi method in improving students’ skill in reading and memorizing Quran for students in grade 2 Islamic Primary School Athirah Bukit Baruga Makassar. The main problem is what the roles of Ummi method in developing students’ skills in reading and memorizing Quran. Then, as for the sub-problem is how to shape the implementation of Ummi method in the process of learning Quran. This study applied qualitative methods by using psychological and pedagogical approach. The researcher conducted this study by collecting data in the field to observe the process of learning Quran with Ummi method. The data was obtained from interviews, observation, and documentation. The data were analyzed and then drawn a conclusion. Then, the findings showed that the learning outcomes of students awarded Very Good based on the evaluation obtained by the students. The reading scores were from 80 until 95. The highest reading score of the students was 95 and the lowest was 80. The memorization scores of the students were from 90 until 95. The lowest score was 90 and the highest one was 95. Based on the data, it can be concluded that the Ummi method used in the second classroom of Athirah Islamic Primary School has a very important role in developing students’ skills in reading and memorizing Quran.